Registry data for cross-country comparisons of migrants' healthcare utilization in the EU: a survey study of availability and content - Krasnik Allan; Nielsen Signe; Rosano Aldo (BMC, 2009)
Abstract Background Cross-national comparable data on migrants' use of healthcare services are important to address problems in access to healthcare; to identify high risk groups for prevention efforts; and to evaluate healthcare systems comparatively. Some of the main obstacles limiting analyses of health care utilization are lack of sufficient coverage and availability of reliable and valid healthcare data which includes information allowing for identification of migrants. The objective of this paper was to reveal which registry data on healthcare utilization were available in the EU countries in which migrants can be identified; and to determine to what extent data were comparable between the EU countries. Methods A questionnaire survey on availability of healthcare utilization registries in which migrants can be identified was carried out among all national statistic agencies and other relevant national health authorities in the 27 EU countries in 2008-9 as part of the Migrant and Ethnic Minority Health Observatory-project (MEHO). The information received was compared with information from a general survey on availability of survey and registry data on migrants conducted by Agency of Public Health, Lazio Region, Italy within the MEHO-project; thus, the information on registries was double-checked to assure accuracy and verification. Results Available registry data on healthcare utilization which allow for identification on migrants on a national/regional basis were only reported in 11 EU countries: Austria, Belgium, Denmark, Finland, Greece, Italy, Luxembourg, the Netherlands, Poland, Slovenia, and Sweden. Data on hospital care, including surgical procedures, were most frequently available whereas only few countries had data on care outside the hospital. Regarding identification of migrants, five countries reported having information on both citizenship and country of birth, one reported availability of information on country of birth, and five countries reported availability of information on citizenship. Conclusion Lack of registry data in 16 EU countries, shortage of data on healthcare utilization, and the diversity in the definition of migrant status hampers cross-national comparisons and calls for an urgent establishment of registries, expansion of the existing registry information, and adoption of a common, generally acceptable definition and identification method of migrants across the EU.